Orofacial Manifestation and Dental Management of Sickle Cell Disease: A Scoping Review. (22nd October 2021) - kakkar, Mayank; Holderle, Kristen; Sheth, Megha; Arany, Szilvia; Schiff, Leslie; Planerova, Adela
Abstract : Aims . Sickle cell disease (SCD) is an upcoming global health problem with rapid progress in therapy especially since 2017. However, systematic reviews found no clinical trials on the dental treatment of sickle cell disease (SCD). This article aims to outline the oral features of the sickle disease and discuss oral management strategies that can serve as guidelines for dental professionals. Material and Methods . A comprehensive literature review was conducted using PubMed, Google Scholar, and Web of Science. The search strategies were developed to cover publications from January 2010 to March 2020. With the help of keywords, multiple abstracts were identified. These abstracts were further reviewed, which included the information about the SCD manifestation, particularly about the oral health features. Based on all these articles and clinical experience, a narrative review was constructed, which summarizes all the aspects of the oral manifestation in people with SCD. Results . The results of this study demonstrate that there is distinct evidence available, indicating the developmental enamel defect leading to hypoplasia and increasing susceptibility to dental caries. Another important result of this review found that people with SCD have a vaso-occlusive crisis in the microcirculation in the dental pulp leading to symptomatic and asymptomatic pulpal necrosis without any signs of odontogenic pathology in an apparently healthy tooth. The study also found that early detection, intervention, and prevention are crucial for improving oral health care, and involving a multidisciplinary approach plays an important role in managing people with SCD. Conclusion . Patients with sickle cell disease have chronic overall health problems. The hematological disorder becomes their main concern and impaired oral health becomes secondary, increasing the risk for dental caries at the most. This paper broadly describes the oral manifestations of SCD, additionally; this paper also provides recommendations for better dental management of patients with SCD. Patients with SCD are often misjudged and, due to lack of knowledge and guidelines, dental providers are not able to provide adequate care. This paper attempts to highlight the essential measures to provide better dental care.